Effect of clay silylation on curing and mechanical and thermal properties of unsaturated polyester/montmorillonite nanocomposites. (December 2015) - Romanzini, Daiane; Frache, Alberto; Zattera, Ademir J.; Amico, Sandro C.
Abstract: This work focuses on the chemical modification of montmorillonite (MMT) (Cloisite® Na) with compatible silanes, vinyltriethoxysilane (CVTES) and γ-methacryloxypropyltrimethoxysilane (CMPS) in order to prevent agglomeration and to improve montmorillonite interaction with an unsaturated polyester resin matrix seeking to achieve a multifunctional composite. Clays were dispersed in the resin by mechanical stirring and sonication and the nanocomposites were prepared by resin transfer into a mold. The mechanical, morphological, thermal and flammability properties of the obtained composites were compared with those prepared using commercial Cloisite® 30B (C30B) and Cloisite® 15A (C15A) clays. Advantages of using silane-modified clays (CVTES and CMPS) as compared with organic-modified clays (C30B and C15A) can be summarized as similar flexural strength and linear burning rate but higher storage modulus and improved adhesion to the polyester resin with consequent higher thermal deflection temperature and reinforcement effectiveness at higher temperatures. However, organic modified clays showed better dispersion (tendency to exfoliate) and consequently delayed thermal volatilization due to the clay barrier effect. Graphical abstract: Highlights: New materials for using in the automotive, building and naval industries. Study this nanocomposite focusing on multifunctional characteristics. Profound discussion in relation to the results obtained.